Hukum Islam dan Kontribusinya terhadap Sistem Hukum di Indonesia - Pribadi, Dimas Pradipta; Bahri, Saiful (ITScience (Information Technology and Science), 2024)
Indonesia is a civil law country and is not based on power. The majority of its population adheres to Islam. Therefore, the formation of the national legal system in Indonesia cannot be separated from religious or Islamic law. Islamic law is a series of doctrines found within the dogmas of Islam, used as a tool to regulate human actions to prevent evil, crime, injustice, corruption, and other harmful behaviors, thus creating security, comfort, welfare, and justice in life. This paper aims to understand the contribution of Islamic law to the national legal system in Indonesia and to examine Islamic law and its contribution to the formation of national law across various aspects. The method used in the preparation of this paper is qualitative through literature study, with sources of information coming from journals, digital books, papers, and materials relevant to the topic. These sources were obtained by the author through internet access and digital books. Islamic law plays an important role and contributes significantly to the formation of national law, including in marriage laws, inheritance, waqf (endowments), the organization of Hajj, zakat management, Islamic banking, religious courts, and special autonomous regions. One area where the influence of Islamic law is strongly felt is family law. This writing demonstrates that Islamic law has become an integral component that enriches the national legal system.